CREATING LEARNING MOTIVATION USING ICE BREAKING IN THEMATIC LEARNING THROUGH VIRTUAL LEARNING IN ISLAMIC ELEMENTARY SCHOOL - Noor Alfi Fajriyani; Marisa Santi Dewi; Abroto Abroto; Yoga Catur Prasetiyo; Yusuf Rendi Wibowo; Faisal Arief Ramadhan (Universitas Pendidikan Indonesia, 2023)
The transition of the teaching system from face-to-face to virtual learning teaching caused problems such as reducing student learning motivation. Since the learning activity is online, students. This study aims to explain the application of ice- breaking through virtual learning in thematic learning can foster student learning motivation. The research method used is a qualitative approach. Assalam Islamic Elementary School of Batu Malang City is the location of the research. Data was collected from informal interview techniques and documentation. The results showed that the application of ice-breaking and its implementation in thematic material through virtual learning in Assalam Islamic Elementary School foster student learning motivation. After giving the ice-breaking, the teacher could build students’ concentration, and the class is conducive. Virtual thematic learning in Assalam Islamic Elementary School using ice-breaking can create positive vibes on student learning motivation.